Optimal chiller loading using improved particle swarm optimization - Nallagownden, P. (Springer Verlag, 2017)
Reducing energy consumption is one of the most important for optimal electric-driven chiller operation. Therefore, even small reduction in power consumption will achieve significant energy savings. This paper adopts improved particle swarm optimization (IPSO), which is aiming to reduce energy consumption, and improve the performance of chillers. The method has been validated by real case study, and the results have demonstrated the effectiveness for saving energy and kept the cooling demand at satisfactory level. © Springer Science+Business Media Singapore 2017.